2010
DOI: 10.1007/s00726-010-0532-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel Fmoc-protected nucleoaminoacid for the solid phase assembly of 4-piperidyl glycine/l-arginine-containing nucleopeptides and preliminary RNA interaction studies

Abstract: In this work, we report the synthesis of a novel Fmoc-protected nucleoaminoacid, based on 4-piperidinyl glycine, carrying the DNA nucleobase on the secondary amino group, suitable for the solid-phase synthesis of nucleopeptides. After ESI-MS and NMR characterization this building block was used for the assembly of a thymine-functionalized tetrapeptide, composed of 4-piperidinyl glycine and L-arginine moieties alternated in the backbone. The ability to interact with RNA and the efficiency in interfering with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Furthermore, Pradhan et al [47] recently found that the phenazinium dye safranin T (Figure 8) recognised singlestranded poly(rA) with great affinity, while it is not able to bind the double-stranded form of the same RNA. Interesting binding results relative to the interaction with poly(rA) of artificial compounds, such as benzodifuran (Figure 9), cationic peptides and nucleoamino acid-based molecules were found by Roviello et al [48][49][50][51][52][53][54][55][56], Moggio et al [57] and Saghyan et al [58]. In particular, regarding the interaction with nucleopeptides ( Figure 10), a significant role was played not only by the molecular recognition of complementary nucleobases, but also by the electrostatic interactions occurring between anionic phosphodiester moieties and the cationic residues present in the nucleo-peptide structures.…”
Section: Synthetic Organic Moleculesmentioning
confidence: 90%
“…Furthermore, Pradhan et al [47] recently found that the phenazinium dye safranin T (Figure 8) recognised singlestranded poly(rA) with great affinity, while it is not able to bind the double-stranded form of the same RNA. Interesting binding results relative to the interaction with poly(rA) of artificial compounds, such as benzodifuran (Figure 9), cationic peptides and nucleoamino acid-based molecules were found by Roviello et al [48][49][50][51][52][53][54][55][56], Moggio et al [57] and Saghyan et al [58]. In particular, regarding the interaction with nucleopeptides ( Figure 10), a significant role was played not only by the molecular recognition of complementary nucleobases, but also by the electrostatic interactions occurring between anionic phosphodiester moieties and the cationic residues present in the nucleo-peptide structures.…”
Section: Synthetic Organic Moleculesmentioning
confidence: 90%
“…Refs. [ 82 , 83 , 84 , 85 ] Nonetheless, nucleoamino acid moieties are found in the natural peptidyl nucleosides [ 86 ], molecules that play a key role in biology and therapy, while a plethora of synthetic nucleoamino acids were developed as building blocks of nucleopeptides [ 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Willardiine In Peptide Structuresmentioning
confidence: 99%
“…[14] They are able to interact with complementary RNA, enhance peptide-peptide recognition, and inhibit the activity of MMLV (Moloney murine leukemia virus) reverse transcriptase by the formation of complexes with polyA at the primer site. [15][16][17] To date, most studies have used NBAs derived from alanine or homoalanine. The corresponding glycine-derived NBAs have been investigated to a much lesser extent, since they have not been synthetically accessible in enantiomerically pure form.…”
Section: Introductionmentioning
confidence: 99%